Find your way with X-Ray: using microCT to correlate in vivo imaging with 3D electron microscopy, chapter 13 - Karreman, Matthia A.; Ruthensteiner, Bernhard; Mercier, Luc; Schieber, Nicole L.; Solecki, Gergely; Winkler, Frank; Goetz, Jacky G.; Schwab, Yannick (Correlative light and electron microscopy III, 2017)
Combining in vivo imaging with electron microscopy (EM) uniquely allows monitoring rare and critical events in living tissue, followed by their high-resolution visualization in their native context. A major hurdle, however, is to keep track of the region of interest (ROI) when moving from intravital microscopy (IVM) to EM. Here, we present a workflow that relies on correlating IVM and microscopic X-ray computed tomography to predict the position of the ROI inside the EM-processed sample. The ROI can then be accurately and quickly targeted using ultramicrotomy and imaged using EM. We outline how this procedure is used to retrieve and image tumor cells arrested in the vasculature of the mouse brain.
Gesehen am 06.09.2021